Slope limit for car with caravan combo / Abdul Rahim Shahor and Azhari Khamis - Shahor, Abdul Rahim; Khamis, Azhari (2001)
This project aim to study about the limitation angle of a slope that car with caravan combo can climb-up. The limitation angle is absolutely different for all kind of drives. The vehicle can be front wheel drive, rear wheel drive or four wheels drives. The limitation angle, 9L is the limit that a car with caravan combo can climb-up. If the slope is over than limitation angle, 6L, the car with caravan combo starts to slide down. From this study, we prefer the formula for limitation angle, GL, by combining all data and basic principle that we get.